Does EUS‐FNA molecular analysis carry additional value when compared to cytology in the diagnosis of pancreatic cystic neoplasm? A systematic review. Issue 5 (27th November 2014) - Gillis, Amy; Cipollone, Ilaria; Cousins, Grainne; Conlon, Kevin
Abstract Background Endoscopic ultrasonography with fine needle aspiration (EUS‐FNA) has become an integral tool in the diagnosis of pancreatic cystic lesions (PCLs) and the analysis of molecular/DNA abnormalities might improve the accuracy of pre‐operative diagnosis. A review was conducted of all studies using EUS‐FNA aspirates of PCLs to assess the accuracy and added benefit that molecular analysis provides to cytological analysis. Methods A systematic review of the literature was conducted using PRISMA guidelines and electronic databases: PubMed/SCOPUS/EMBASE/Cochrane/CINAHL. Surgical pathology was used as the definitive reference standard. The QUADAS‐2 tool was used for quality assessment. Results In total, 162 articles were identified; 12 articles met inclusion/exclusion criteria. Ten studies reported on cytology and 8 studies reported k‐ras mutational analysis. 362 patients (of 1115 total) had surgical pathology available. The sensitivity and specificity of cytology was 0.42 and 0.99; the sensitivity and specificity of k‐ras was 0.39 and 0.95; and the sensitivity and specificity of the combined test of cytology and k‐ras was 0.71 and 0.88, respectively. Conclusions k‐ras mutational analysis used as an individual screening test has a poor diagnostic accuracy, as does cytology when used alone. The benefit comes with utilization in a combined fashion. More studies are needed to evaluate the correct sequence and utility of these tests for cyst differentiation.